Optimal. Leaf size=18 \[ e^{-3+e-x} \left (4-\frac {2 x^2}{3}\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.07, antiderivative size = 26, normalized size of antiderivative = 1.44, number of steps used = 10, number of rules used = 5, integrand size = 36, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.139, Rules used = {12, 21, 2196, 2194, 2176} \begin {gather*} 4 e^{-x+e-3}-\frac {2}{3} e^{-x+e-3} x^2 \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 21
Rule 2176
Rule 2194
Rule 2196
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {1}{3} \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{-6+x^2} \, dx\\ &=-\left (\frac {2}{3} \int e^{-3+e-x} \left (6+2 x-x^2\right ) \, dx\right )\\ &=-\left (\frac {2}{3} \int \left (6 e^{-3+e-x}+2 e^{-3+e-x} x-e^{-3+e-x} x^2\right ) \, dx\right )\\ &=\frac {2}{3} \int e^{-3+e-x} x^2 \, dx-\frac {4}{3} \int e^{-3+e-x} x \, dx-4 \int e^{-3+e-x} \, dx\\ &=4 e^{-3+e-x}+\frac {4}{3} e^{-3+e-x} x-\frac {2}{3} e^{-3+e-x} x^2-\frac {4}{3} \int e^{-3+e-x} \, dx+\frac {4}{3} \int e^{-3+e-x} x \, dx\\ &=\frac {16}{3} e^{-3+e-x}-\frac {2}{3} e^{-3+e-x} x^2+\frac {4}{3} \int e^{-3+e-x} \, dx\\ &=4 e^{-3+e-x}-\frac {2}{3} e^{-3+e-x} x^2\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.01, size = 19, normalized size = 1.06 \begin {gather*} \frac {2}{3} e^{-3+e-x} \left (6-x^2\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.63, size = 16, normalized size = 0.89 \begin {gather*} e^{\left (-x + e + \log \left (-\frac {2}{3} \, x^{2} + 4\right ) - 3\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.21, size = 24, normalized size = 1.33 \begin {gather*} -\frac {2}{3} \, x^{2} e^{\left (-x + e - 3\right )} + 4 \, e^{\left (-x + e - 3\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.15, size = 17, normalized size = 0.94
method | result | size |
gosper | \({\mathrm e}^{\ln \left (-\frac {2 x^{2}}{3}+4\right )+{\mathrm e}-3-x}\) | \(17\) |
norman | \({\mathrm e}^{\ln \left (-\frac {2 x^{2}}{3}+4\right )+{\mathrm e}-3-x}\) | \(17\) |
risch | \(\left (-\frac {2 x^{2}}{3}+4\right ) {\mathrm e}^{{\mathrm e}-3-x}\) | \(17\) |
default | \(\text {Expression too large to display}\) | \(5846\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.42, size = 21, normalized size = 1.17 \begin {gather*} -\frac {2}{3} \, {\left (x^{2} e^{e} - 6 \, e^{e}\right )} e^{\left (-x - 3\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.14, size = 16, normalized size = 0.89 \begin {gather*} -\frac {2\,{\mathrm {e}}^{-x}\,{\mathrm {e}}^{-3}\,{\mathrm {e}}^{\mathrm {e}}\,\left (x^2-6\right )}{3} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.12, size = 15, normalized size = 0.83 \begin {gather*} \frac {\left (12 - 2 x^{2}\right ) e^{- x - 3 + e}}{3} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________